Juridical Analysis of the Criminal Act of Sexual Harassment by Medical Personnel in the Perspective of Progressive Law and the New Criminal Code - Ranny Iwan Susilo; Hendriadi Yustin; Wa Marcella; Alex Togaraja Simanjorang; Edy Santoso (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study discusses the juridical analysis of the criminal act of sexual harassment by medical personnel from the perspective of progressive law and the New Criminal Code (KUHP). The case of sexual harassment by medical personnel in Garut in 2025 is the background for this study, which shows the abuse of power relations between medical personnel as the dominant party and the patient as the vulnerable party. This study aims to analyze how law enforcement of the case is reviewed from progressive legal theory and its conformity with the provisions of the New Criminal Code and the Sexual Violence Crime Law. The research method used is normative legal research with a statutory approach, a conceptual approach, and a case approach, and is analyzed qualitatively. The results of the study show that although law enforcement has resulted in criminal verdicts and restitution for victims, the process is still influenced by the phenomenon of no viral, no justice, so it does not fully reflect substantive justice. Based on the progressive legal theory put forward by Satjipto Rahardjo, the law should not only be oriented to legal certainty, but also to the protection and recovery of victims as a whole. Therefore, it is necessary to strengthen the progressive legal paradigm in law enforcement in order to create a more responsive, humane, and just legal system for victims.